Hubungan Pemberian Susu Formula Dengan Kejadian Diare Pada Bayi di Ruang Dahlia RSUD Dr. H. Soewondo Kendal - Tri Sakti Widyaningsih (LPPM STIKES Guna Bangsa Yogyakarta, 2018)
Background: Diarrhea is an increase in the number, frequency,and fluidity (level of dilution) of feces.Diarrhea can be acute and chronic. Chronic diarrhea is usually caused by chronic conditions, such as lactose intolerance. Early formula feeding can cause diarrhea in infants. Phenomena that occurred in Dahlia Room RSUD Dr. H. Soewondo Kendal is a lot of moms give formula milk to their baby and have diarrhea. This research aims to the relationship of formula feeding with diarrhea occurrence in infants.